Access, understanding, promotion and maintenance of good health: Evaluation of knowledge transfer of people with intellectual disabilities to bridge the health information and disease prevention in public health - Dam, Lisa T.; Heidler, Petra; King, Isabel (Frontiers in Public Health, 2022)
The importance of patient empowerment among people with intellectual disabilities (ID) is steadily growing, yet, there are still multiple health and health literacy challenges that make this population more vulnerable to health disparities. Inadequate access to essential health and other basic services and a lack of involvement in health and educational research are some of the most crucial factors contributing to this inequality, and greater effort has to be made to include people with ID in health literacy and communication research, preliminary focusing on language, including pictorial language. This community case study aimed to document the experiences of answering a pilot questionnaire to evaluate the problems of people with mild to moderate ID, 6A00.0 and 6A00.1 according to ICD-11. Our results indicate that semi-structured interviews with a trained interviewer might be most suitable for measuring the knowledge transfer of people with ID. Furthermore, this case study highlights the need to develop an appropriate questionnaire and emphasises the need for continued dialogue between people ID and healthcare providers.